THE ISLAMIC CENTRE OF MUADZ BIN JABAL OF KENDARI - Saprillah Syahrir (JICSA : Journal of Islamic Civilization in Southeast Asian, 2017)
Salafism has become an interesting phenomenon in recent years in Indonesia, including in Southeast Sulawesi. The presence of Salafi groups in Kendari wins an enthusiastic welcome from the society. This research is intended to describe the role of the Islamic Center of Muadz bin Jabal (ICM) in managing da’wah (Islamic missionary) and religious education in Kendari City. This study employs qualitative research methods. Data are obtained through interviews and observations. The research findings indicate that the Islamic Center of Muadz bin Jabal or ICM is one of the Salafi groups that have quite influential da’wah and educational roles in Kendari City. The ICM manages its ideology and religious knowledge through educational institutions, da’wah assemblies, radio broadcast, and face book.